2022
DOI: 10.1111/ajo.13555
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study comparing neonatal outcomes of waterbirth and land birth in an Australian tertiary maternity unit

Abstract: Background: Maternal preference for warm water immersion (WWI) and waterbirth is increasing, but adoption into obstetric guidelines and clinical practice remains limited. Concerns regarding safety and a paucity of evidence have been cited as reasons for the limited adoption and uptake. Aim:The aim was to investigate maternal and neonatal outcomes after WWI and/ or waterbirth compared with land birth. Materials and methods: A prospective cohort study was conducted in anAustralian public maternity hospital betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Two studies (Seed et al, 2023;Sidebottom et al, 2020) showed no significant difference between the hydrotherapy and control groups in terms of the use of pain medication (Z = 0.21, p = 0.840).…”
Section: Meta-analysis Results Related To the Effects Of Hydrotherapy...mentioning
confidence: 97%
See 4 more Smart Citations
“…Two studies (Seed et al, 2023;Sidebottom et al, 2020) showed no significant difference between the hydrotherapy and control groups in terms of the use of pain medication (Z = 0.21, p = 0.840).…”
Section: Meta-analysis Results Related To the Effects Of Hydrotherapy...mentioning
confidence: 97%
“…Eight studies (Barry et al, 2020;Darsareh et al, 2018;Lanier et al, 2021;Lewis et al, 2018;Liu et al, 2014;Neiman et al, 2020;Seed et al, 2023;Tas ¸kın & Ergin, 2022) Five studies (Darsareh et al, 2018;Lewis et al, 2018;Seed et al, 2023;Tas ¸kın & Ergin, 2022;Zhao et al, 2017) showed that compared to the control group, the likelihood of assisted vaginal birth was lower in the hydrotherapy group (Z = 5.65, p < 0.001). This significant effect was associated with observational studies.…”
Section: Meta-analysis Results Related To the Effects Of Hydrotherapy...mentioning
confidence: 99%
See 3 more Smart Citations